Anti-Corruption Education Policy Outputs for Combatting Corruption in Indonesia: Applying the Theory of Planned Behaviour - Dyah Lituhayu; Amni Zarkasyi Rahman; Mujibur Rahman Khairul Muluk; Mohammad Nurul Huda (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2023)
Corruption is a bureaucratic disease that has become as entrenched as the common cold, undermining governments globally. Proactive government policies can reduce corruption crimes through prosecution, prevention and education. The Indonesian government has implemented a ‘trident’ corruption eradication policy in educational institutions aiming to shape the attitudes, norms and behaviour of the nation’s younger generation. Unfortunately, the existing literature is limited in assessing the policy output of preventing and eradicating corruption, particularly the effectiveness of anti-corruption education among university students. A policy output evaluation perspective is offered to fill this research gap. This study aims to evaluate the policy output of anti-corruption education in shaping attitudes, norms and behaviour using the theory of planned behaviour. A quantitative approach and survey method were chosen, and a total of 125 respondents participated. The partial least squares algorithm and bootstrapping methods were used to analyse the data. The study’s results reveal that perceived behaviour control, attitude, subjective norm have significant influences on students’ intention. Perceived behaviour control has significant influences on students’ anti-corruption behaviour, though attitudes do not affect students’ anti-corruption behaviour. The findings also show that it has a good level of effectiveness in anti-corruption education policy outputs in achieving policy goals. Our policy recommendations include socialisation about anti-corruption to the community, implementing ideology education and upholding the law on corruption to increase the success of corruption prevention and eradication policies.